Converting ab initio energies to enthalpies of formation of free radicals. I. new atom equivalents for alkyl radicals - Bhattacharya, Arijit (Aiche Journal, 2012)
A simple method is presented to convert ab initio computed total energies to the standard enthalpy of formation (Delta H-f(o)) of a large number of saturated alkyl radicals (especially those that are relatively highly branched), for which experimental data are scarcely available. For this purpose a new set of radical atom-equivalents (AEQ) and their unique combinations were defined and the energy values of the latter assigned. The theory level and the basis set requirement for the quantum chemistry calculation of the molecular energy were found to be moderate. The Delta H-f(o) predictions appear to be quite accurate with reference to limited available experimental data and are better than values calculated by the group-additivity and the difference methods. The strategy provides an inexpensive way of harnessing the power of computational chemistry and combining it with the organization and insight from the group-additivity method sans any empirical corrections. (C) 2011 American Institute of Chemical Engineers AIChE J, 58: 600-609, 2012
Keywords: atom-equivalents; computational chemistry; enthalpy of formation; free radicals; goup additivity method